2006
DOI: 10.1111/j.1600-0560.2006.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of dormant cutaneous Leishmania infection in a kidney transplant patient

Abstract: To our knowledge, this is the first case of cutaneous leishmaniasis in a kidney transplant patient residing in the US in an area known to be non-endemic for leishmaniasis, probably after reactivation of a previously dormant infection acquired outside of the US at least 9 months prior to developing clinical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…In 2006, Mirzabeigi et al reported reactivation of cutaneous leishmaniasis in a female patient after kidney transplantation [8]. The patient had a dormant Leishmania infection prior to renal transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006, Mirzabeigi et al reported reactivation of cutaneous leishmaniasis in a female patient after kidney transplantation [8]. The patient had a dormant Leishmania infection prior to renal transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In the Giemsa stained slide, amastigotes were shown in histiocytes. In this patient, reactivation of cutaneous leishmaniasis was due to high doses of immunosuppressive drugs after transplantation [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow or solid organ transplantation [89][90][91][92][93][94][95] and therapy with immunosuppressive or biologic drugs [96][97][98] also have been associated with the appearance of ATL. In immunosuppressed patients, CL is characterized by atypical cutaneous lesions and persistent negativity of diagnostic tests 91 .…”
Section: Resultsmentioning
confidence: 99%
“…Cutaneous disease is less common than visceral or mucosal disease in transplant recipients, with reports of two cases of classic disease, one case of disseminated disease caused by Leishmania major , one case of nodular disease, and two cases (one a recurrence) of post-Kala-Azar dermal leishmaniasis caused by Leishmania infantum [ 45 ]. A case of reactivation of a dormant cutaneous Leishmania infection in a renal transplant recipient from Bolivia who had undergone a renal transplant 2 months earlier and was living in a nonendemic area serves as a valuable teaching point about latent infection [ 46 ].…”
Section: Parasitic Skin and Soft Tissue Infectionsmentioning
confidence: 96%